Use of Sludge as Ceramic Materials - Morais, L. C. [UNESP]; Vianna, R. S. C. [UNESP]; Campos, V. [UNESP]; Fraceto, L. F. [UNESP]; Rosa, André Henrique [UNESP]; Buechler, P. M. (Trans Tech Publications Ltd, 2010)
Nowadays, with increase amounts of sludge derived from the treatment of domestic sewage put pressure into research on systems for the adequate use of these materials. The aim of the present work is to study the use of sludge ash, from sintering and calcinated process, as a raw material for the ceramic industry. Using the sewage sludge ashes as ceramic raw material there will be no contamination of soil and underground water. Metals and toxic compounds like Al, Fe, Ba, Cr, Cu, Mn and Zn oxides were analyzed and characterized by X-ray fluorescence (XRF), scanning electron microscopy (SEM) and plasma emission spectroscopy (ICP-OES). The leached material was chemically analyzed where the integration of oxides into the ceramic matrix of sludge ash was observed. Residual decomposition was analyzed by TG, DTG and DTA curves.
Keywords: sewage sludge ash; oxide integration; scanning electron microscopy; ceramic materials